(3GdMLI hGdGfJUGQ aj Ydd GdbQGAGJ dCgd GdCeUGQs - (3GHf NGdhjg , GdMSjf Hf CMeO Hf NGdhjg Hf MeOGf, CHh YHO Gddg,J (B370 (3g` s
(3ChdgG (B:s
(3hHYO aEfj JOHQJ bQGAI GdCFeI GdSHYI ef Cgd GdCeUGQ GdNeSI bO PgH aj EYQGH eG GfaQO Hg ef MQag s
(3BNQgG (B:s
(3HhUd GdCda GdChdi hbWY s
(3GdehLhO efg bWYI ef Ghdg Edi CKfGA ShQI Wgs
(3GdfSNI HgG MhGTs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B155 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B175s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs